2009
DOI: 10.1007/s12017-009-8058-1
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Prevents NAD+ Depletion and Protects Neurons Against Excitotoxicity and Cerebral Ischemia: NAD+ Consumption by SIRT1 may Endanger Energetically Compromised Neurons

Abstract: Neurons require large amounts of energy to support their survival and function, and are therefore susceptible to excitotoxicity, a form of cell death involving bioenergetic stress that may occur in several neurological disorders including stroke and Alzheimer's disease. Here we studied the roles of NAD + bioenergetic state, and the NAD + -dependent enzymes SIRT1 and PARP-1, in excitotoxic neuronal death in cultured neurons and in a mouse model of focal ischemic stroke. Excitotoxic activation of NMDA receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
205
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(212 citation statements)
references
References 72 publications
4
205
2
1
Order By: Relevance
“…In the present study, SIRT1 expression was unaffected by age and ischemic injury in vehicle-treated mice. This is in contrast with a previous report that found elevated cortical SIRT1 protein levels 3 h after stroke (Liu et al 2009a). This same study found a decrease at 6 h in SIRT1 protein, and differences may reflect the timing of evaluation (at 4 and 24 h in our study).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, SIRT1 expression was unaffected by age and ischemic injury in vehicle-treated mice. This is in contrast with a previous report that found elevated cortical SIRT1 protein levels 3 h after stroke (Liu et al 2009a). This same study found a decrease at 6 h in SIRT1 protein, and differences may reflect the timing of evaluation (at 4 and 24 h in our study).…”
Section: Discussioncontrasting
confidence: 99%
“…AMPK enhances SIRT1 activity by increasing cellular NAD+ levels (Canto et al 2009). Although it has been suggested that increased SIRT1 activity leads to extension of life span (Howitz et al 2003;Wood et al 2004), what role SIRT1 plays in the response to ischemic brain insults is unknown (Raval et al 2008;Liu et al 2009a). In the present study, SIRT1 expression was unaffected by age and ischemic injury in vehicle-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…This unorthodox hypothesis is consistent with our findings and the suggestion of others that in a variety of contexts, effects of NAM on NAD ϩ synthesis may overcome sirtuin inhibition with resulting net activation of NAD ϩ -dependent sirtuin activity (27, 40 -42). It has been reported, for example, that NAM improved suppression of neuronal SIRT1 deacetylase activity by G/N glutamate (43). A possible additional explanation of this observation is that NAM has suppressive effects on acetyltransferase activity, although this will require further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…206,207 Cerebral ischemia results in altered SIRT1 protein and activity levels in brain. 208 Sirtuin activity is reduced within the first 6 hours after ischemic injury, but is then is increased at 12 and 24 hours. Resveratrol, a potent SIRT1 activator, has neuroprotective effects in cerebral ischemia, 209 -211 but whether this effect is mediated through actions on microglia remains to be established.…”
Section: Other Factors That Influence Proinflammatory Gene Transcriptionmentioning
confidence: 99%